SEREN TAUN DAN MODERNISASI DALAM EKSPRESI DRYWALL - Gina Novi Ambia (ATRAT: Jurnal Seni Rupa, 2019)
Seren Taun is a tradition who author still preserve because of this tradition have purpose to have a gratitude about what God give to mankind in this earth. Not only that, The Seren Taun teach a mankind to have a sense of care to fellow of us, care of the nature, and the most important thing is to make us become more obedient to our faith of our God according our each faith. In this modern age, mostly a mankind forgotten about a tradition so much of them lost their identity and impact to the their life, such as individuality character an less of care to their environment or nature so disaster of nature is everywhere, and less care of fellowship who impact to much of hostility and action of immorality and then the author critize about that point with creating a artworks with the technique of drywall art sculpture. The vizual who displayed is a figure of mankid with Seren Taun tradition and figure of mankid in modern of age, so are displayed a figure in myth that is Godess Sri Pohaci and added with a modern elements. Keywords: Seren Taun, Modernization. Drywall, Gypsum________________________________________________________________ Tradisi Seren Taun bertujuan untuk mengucapkan rasa syukur terhadap apa yang sudah diberikan Tuhan kepada manusia di bumi ini, bukan hanya itu tetapi Seren Taun juga mengajarkan manusia untuk lebih peduli terhadap sesama manusia, terhadap alam, dan menjadikan manusia lebih taat  kepada Tuhan. Di zaman modern ini manusia banyak yang sudah melupakan tradisi sehingga banyak pula yang kehilangan jati diri dan berdampak pada kehidupan seperti sikap individualis dan tidak peduli kepada sesama manusia, selain itu juga kurang peduli dengan lingkungan sehingga banyak terjadi bencana. Berdasarkan fenomena yang ada, maka dibuatlah karya dengan teknik drywall art sculpture sebagai bentuk kritik terhadap fenomena tersebut. Visual yang ditampilkan yaitu figur manusia dengan tradisi Seren Taun dan figur manusia di zaman modern, serta menampilkan sosok mitos Dewi Sri Pohaci dengan menambahkan unsur modern.Kata Kunci: Seren Taun, Modernisasi, Drywall, Gypsum